Right to Food and Food Security – An Indian Perspective: Examining the Challenges of Ensuring Food Security in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Food demand increase is due mainly to changing food consumption patterns and population growth. Our main concern for the food and agricultural sector is to provide sufficient amount food, to meet the nutritional needs of the ever growing population. Food production and its physical availability are certainly essential to addressing hunger. However, producing more food alone will not be sufficient to achieve food and nutritional security. In fact, food and nutrition security is about more than just producing sufficient food as it encompasses the need to ensure access to food at all times.